A Combined Theory‐Experiment Analysis of the Surface Species in Lithium‐Mediated NH3 Electrosynthesis. Issue 7 (1st April 2020) - Schwalbe, Jay A.; Statt, Michael J.; Chosy, Cullen; Singh, Aayush R.; Rohr, Brian A.; Nielander, Adam C.; Andersen, Suzanne Z.; McEnaney, Joshua M.; Baker, Jon G.; Jaramillo, Thomas F.; Nørskov, Jens K.; Cargnello, Matteo
Abstract: Invited for this month's cover picture is the group of Prof. Matteo Cargnello in the Chemical Engineering Department at Stanford University and within the SUNCAT Center for Interface Science and Catalysis (USA). The cover picture shows nitrogen molecules being reduced to ammonia on a lithium‐covered surface. Read the full text of the Article at 10.1002/celc.201902124 . Abstract : "Electrochemical processes for ammonia synthesis could potentially replace the high temperature and pressure conditions of the Haber–Bosch process, with voltage offering a pathway to distributed fertilizer production that leverages the rapidly decreasing cost of renewable electricity. However, nitrogen is an unreactive molecule and the hydrogen evolution reaction presents a major selectivity challenge. An electrode of electrodeposited lithium in tetrahydrofuran solvent overcomes both problems by providing a surface that easily reacts with nitrogen and by limiting the access of protons with a nonaqueous electrolyte…" Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding Article at 10.1002/celc.201902124 .